2009
DOI: 10.1002/ejic.200900858
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II)‐Promoted [2+3] Cycloaddition of Azide with 4‐Cyanobenzaldehyde, a Schiff Base Derivative or Dicyanobenzenes To Give Formyl‐, Amino(imino)‐ or Cyano‐Functionalized Tetrazolato Complexes

Abstract: The [2+3] cycloaddition reaction (which is greatly accelerated by microwave irradiation) of the bis(azido)platinum(II) compound cis‐[Pt(N3)2(PPh3)2] (1) with 4‐cyanobenzaldehyde (2) furnishes the N2N2‐bonded isomer of bis[5‐(4‐formylphenyl)tetrazol‐2‐ate] platinum(II) trans‐[Pt{N4CC6H4(4‐CH=O)}2(PPh3)2] (3a) as the major product, along with the N1N2‐bonded isomer 3b. Treatment of 3a with 2‐dimethylaminoethylamine (4), in refluxing methanol, gives the corresponding N2N2‐bonded bis[(E)‐5‐(4‐{[2‐(dimethylamino)et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The pentafluorophenyl ring lies perpendicular to the plan constructed by the Pt-, P- and Cl-atoms (89.8°). The bond lengths involving the metal and the donor atoms (see Figure 1, legend), are within those found in other Pt(II) compounds [94,95,96,97,98,99]. No classical H-bond interactions could be found in 2a , but the shortest C–H⋅⋅⋅N interactions (Figure 1) expand the structure to the third dimension.…”
Section: Resultssupporting
confidence: 75%
“…The pentafluorophenyl ring lies perpendicular to the plan constructed by the Pt-, P- and Cl-atoms (89.8°). The bond lengths involving the metal and the donor atoms (see Figure 1, legend), are within those found in other Pt(II) compounds [94,95,96,97,98,99]. No classical H-bond interactions could be found in 2a , but the shortest C–H⋅⋅⋅N interactions (Figure 1) expand the structure to the third dimension.…”
Section: Resultssupporting
confidence: 75%
“…For example, we have shown [17] that the di(azido) complexes of the type cis-[Pt(N 3 ) 2 (PPh 3 ) 2 ] can react with nitriles NCR to give the bis(tetrazolato) compounds trans-[Pt(N 4 CR) 2 (PPh 3 ) 2 ] from which the tetrazoles can be liberated. Very recently, we have reported that [2 þ 3] cycloaddition of cis-[Pt(N 3 ) 2 (PPh 3 ) 2 ] with 4-cyanobenzaldehyde furnishes a (formylphenyl)tetrazolate complex that reacts with 2-dimethylaminoethylamine to give the corresponding Schiff base derivative, the latter undergoing hydrolysis in the presence of a metal salt, while the reactions of di(azido) complexes with dicyanobenzenes give (cyanophenyl)tetrazolate complexes [18]. In addition, the reactions of bis(tetrazolato)-Pt II compounds with propionitrile furnish mono-or dicyano-complexes, via an unusual oxidative addition involving NCeC bond cleavage of one or two propionitrile molecules, respectively [17aec].…”
Section: Introductionmentioning
confidence: 99%
“…This activation allows the performance of CA in water or water/alcohol mixtures, but usually prolonged heating is still necessary. Metal-mediated CA is also known, and it is typically conducted by two routes, viz., CA of free azides to coordinated nitriles (for recent works see refs ) or metal-bound azides to uncomplexed nitriles (for recent works see refs ). Some metal-mediated syntheses allow the generation of coordinated tetrazoles rapidly already at room temperature (RT). , Furthermore, CAs of azide ions to highly reactive alkylnitrilium salts were reported, and these reactions form 1,5-disubstituted tetrazoles at RT. , Several cases of BF 3 -catalyzed CA of azides to nitriles, except one example of intramolecular CA, require prolonged heating, and they are not recommended for synthetic purposes. …”
Section: Resultsmentioning
confidence: 99%